Low-oxygen superfine tantalum powder and preparation method thereof

Through two hydrogenation and subsequent powder, ball mills, pickles, and low -temperature dehydrogenation of oxygen reduction of hydrogenation, ball mill, pickling, and low -temperature dehydrogenation, the problems that are difficult to meet at the same time in the existing technologies have achieved granularity The preparation of low oxygen ultra -fine powder with fine and oxygen content meets the high requirements of metallurgical powder.

CN119368721AActive Publication Date: 2025-01-28NINGXIA ORIENT TANTALUM INDUSTRY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411444703.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art is difficult to meet the fine-grained and low-oxygen content requirements of metallurgical grade tantalum powder at the same time, resulting in unstable performance in some application scenarios.

Method used

Through the two hydrogenation treatment of high -purity ingots, the contact area of ​​metal and hydrogen is increased, and then powder -making, ball milling, pickling and low -temperature dehydrogenurative oxygen reduction is performed. Powder.

Benefits of technology

The application field of metallurgical -grade powder to meet the requirements of metallurgical -grained pink powder and oxygen content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005087398460000011
    Figure HDA0005087398460000011
Patent Text Reader

Abstract

The invention provides low-oxygen superfine tantalum powder and a preparation method thereof, and relates to the technical field of tantalum powder preparation, the oxygen content of the tantalum powder is smaller than 2000 ppm, the difference value between the particle size D90 and the particle size D50 of the tantalum powder is 2-5 microns, the particle size distribution is narrow, the powder is uniform, the particle size of the tantalum powder is small, the performance is stable, and the application field of metallurgical-grade powder with higher requirements for the particle size and the oxygen content can be met. And on the other hand, tantalum has brittleness by hydrogenating the tantalum ingot twice, and the particle size of tantalum powder meets the requirement by selecting proper meshes and controlling the ball milling time during crushing and powdering. Impurities introduced in the ball milling process are removed through acid pickling, and superfine tantalum powder is obtained through drying; and the low-oxygen superfine tantalum powder is obtained through subsequent low-temperature dehydrogenation and oxygen reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tantalum powder preparation, and specifically relates to low-oxygen ultrafine tantalum powder and a preparation method thereof. Background Art

[0002] Tantalum is a rare metal that is regarded as an emerging strategic metal. Due to its high melting point, high dielectric constant, good hardness, high plasticity, excellent thermal conductivity and electrical conductivity, tantalum capacitors have a wide operating temperature range, high reliability, shock resistance and long service life, and have broad application prospects in many high-tech fields.

[0003] Metallurgical tantalum powder is mainly used to prepare various tantalum materials, copper wires of integrated circuits, sputtering targets for barrier layers between silicon, alloy additives, and the medical industry; the quality of metallurgical-grade tantalum powder is mainly evaluated from the physical properties and chemical composition, including the particle size distribution, particle morphology, chemical impurities, and bulk density of the tantalum powder. Generally, only special requirements are made for the D50 of metallurgical-grade tantalum powder, but in special application scenarios, requirements are also made for the D50, D90, and oxygen content of metallurgical-grade tantalum powder. Usually, tantalum powder with a finer particle size is more active and is easily reacted with oxygen, nitrogen, etc. when exposed to air at room temperature, which increases the oxygen content in the tantalum powder; although the oxygen content can be reduced by deoxidation, the deoxidation process will cause the material to sinter, causing the particle size of the material to increase, resulting in certain limitations in the industrial production of low-oxygen ultrafine tantalum powder.

[0004] In the prior art, for example, a Chinese invention patent with application number 201480016668.3 discloses a high-purity tantalum powder and a preparation method thereof. The GDMS analysis purity of the tantalum powder is greater than 99.995%, the oxygen content is not higher than 1000 ppm, the nitrogen content is not higher than 50 ppm, the hydrogen content is not higher than 20 ppm, the magnesium content is not higher than 5 ppm, and the particle size D50 is less than 25 μm. In the patent, the particle size of the tantalum powder is given to be less than 25 μm, and D50 is relatively large. However, it is well known to those skilled in the art that when D50 is less than 10 μm, the specific surface area of ​​the tantalum powder is relatively large, and it is easy to adsorb oxygen in the air, resulting in a high oxygen content. Therefore, it is necessary to provide a tantalum powder with a small particle size and low oxygen content and a preparation method thereof. Summary of the invention

[0005] In view of this, the present invention provides a low-oxygen ultrafine tantalum powder.

[0006] It is also necessary to provide a method for preparing low-oxygen ultrafine tantalum powder.

[0007] The technical solution adopted by the present invention to solve its technical problem is: A low-oxygen ultrafine tantalum powder, the oxygen content of the tantalum powder is less than 2000ppm, and the difference between the particle size D90 and D50 of the tantalum powder is 2-5um.

[0008] Preferably, the particle size D50 of the tantalum powder is 3-5 um.

[0009] Preferably, the particle size D90 of the tantalum powder is 6-9 um.

[0010] The method for preparing low-oxygen ultrafine tantalum powder as described above, wherein the low-oxygen ultrafine tantalum powder is prepared by the following steps: S1: The high-purity tantalum ingot is subjected to two hydrogenation treatments, and the second hydrogenation temperature is 100°C-400°C lower than the first hydrogenation temperature, so as to increase the contact area between the metal and hydrogen after the high-purity tantalum ingot is defilmed, ensure thorough hydrogenation, and obtain high-brittle high-purity tantalum powder after hydrogenation; S2: Powdering, ball milling, pickling, filtering and drying the hydrogenated high-brittle high-purity tantalum powder to obtain a first crude tantalum powder; S3: adding a reducing agent to the first crude tantalum powder, and then dehydrogenating and deoxygenating the first crude tantalum powder at 700° C.-900° C. to obtain a second crude tantalum powder; S4: acid-washing, filtering and drying the second tantalum powder crude product to obtain low-oxygen ultrafine tantalum powder.

[0011] Preferably, in step S1, the insulation temperature of the first hydrogenation treatment is 1000°C-1100°C for 4h-6h, and the insulation temperature of the second hydrogenation treatment is 700°C-900°C for 8-12h.

[0012] Preferably, in the step S1, the high-purity tantalum ingot is only in contact with hydrogen and not with other gases during the two hydrogenation processes.

[0013] Preferably, in step S1, the heating rate of the first hydrogenation treatment is 20°C / min-30°C / min, and the heating rate of the second hydrogenation treatment is 5°C / min-10°C / min.

[0014] Preferably, in the step S3, the reducing agent is magnesium powder, and the amount of the magnesium powder added is 0.5-2.0% of the weight of the first crude tantalum powder.

[0015] Preferably, in the step S3, the heating rate of the dehydrogenation and oxygen reduction is 10°C / min-20°C / min, and argon gas is introduced for protection during the heating process.

[0016] Preferably, in the step S2, the powder making is specifically: crushing the hydrogenated high-brittle high-purity tantalum powder, and screening to obtain the hydrogenated high-brittle high-purity tantalum powder with a mesh size of 100-400.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a low-oxygen ultrafine tantalum powder, the oxygen content of the tantalum powder is less than 2000ppm, and the difference between the particle size D90 and D50 of the tantalum powder is 2-5um, indicating that the particle size distribution is narrow, the powder is uniform, the particle size of the tantalum powder is fine, and the performance is stable, which can meet the application fields where metallurgical-grade powder has higher requirements on particle size and oxygen content.

[0018] The present invention also provides a method for preparing low-oxygen ultrafine tantalum powder, which makes the tantalum brittle by hydrogenating the tantalum ingot twice, selects a suitable sieve when crushing and powdering, and controls the ball milling time to make the tantalum powder particle size meet the requirements. Impurities introduced during the ball milling process are removed by acid washing, and ultrafine tantalum powder is obtained by drying; low-oxygen ultrafine tantalum powder is obtained by subsequent low-temperature dehydrogenation and oxygen reduction.

[0019] The present invention quickly removes the tantalum pentoxide layer on the surface of the high-purity tantalum ingot through the first hydrogenation, so that the surface of the high-purity tantalum ingot is kept clean. At the same time, the high-purity tantalum ingot undergoes a hydrogenation reaction with hydrogen to generate a hydride layer. As the contact area increases, the hydride layer transfers hydrogen. At high temperature, the reaction rate increases, and the generated hydride layer no longer adheres to the surface, resulting in cracks and fissures, so that the crushing contact area of ​​the high-purity tantalum ingot is further increased, and the high-purity tantalum ingot is changed into small particles. Then, the second hydrogenation is performed. Under the condition of saving energy, the second hydrogenation is performed at a lower temperature. The second hydrogenation increases the contact area between the metal and hydrogen, ensures that the tantalum powder is thoroughly embrittled by hydrogenation, and prepares a powder with a finer particle size and more uniformity.

[0020] High-purity tantalum ingots are body-centered cubic crystals, and tantalum hydride (TaH) after hydrogen absorption is a body-centered cubic lattice. The first hydrogenation allows hydrogen to quickly enter the lattice positions, causing the original lattice lattice to expand and rupture, and then the second hydrogenation is performed to further increase the contact area, causing the tantalum ingot to fall off layer by layer, and finally forming tantalum powder with a smaller particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the particle size distribution diagram of the low-oxygen ultrafine tantalum powder sample D in Example 1.

[0022] Figure 2 This is the particle size distribution diagram of the low-oxygen ultrafine tantalum powder sample d of Example 2.

[0023] Figure 3 This is the particle size distribution diagram of tantalum powder sample A in comparative example 1.

[0024] Figure 4 This is the particle size distribution diagram of tantalum powder sample B in comparative example 2.

[0025] Figure 5 This is the particle size distribution diagram of tantalum powder sample C in comparative example three.

[0026] Figure 6 This is the particle size distribution diagram of tantalum powder sample E in comparative example 4.

[0027] Figure 7 This is a scanning electron microscope image of the low-oxygen ultrafine tantalum powder sample D of Example 1.

[0028] Figure 8 This is a scanning electron microscope image of the low-oxygen ultrafine tantalum powder sample d of Example 2.

[0029] Fig. 9 This is a scanning electron microscope image of tantalum powder sample A in comparative example 1.

[0030] Fig.10 This is a scanning electron microscope image of tantalum powder sample B in comparative example 2.

[0031] Fig.11 This is a scanning electron microscope image of tantalum powder sample C in comparative example three.

[0032] Fig.12 This is a scanning electron microscope image of tantalum powder sample E in comparative example 4. DETAILED DESCRIPTION

[0033] The technical solutions and technical effects of the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings of the present invention.

[0034] A low-oxygen ultrafine tantalum powder, the oxygen content of the tantalum powder is less than 2000ppm, and the difference between the particle size D90 and D50 of the tantalum powder is 2-5um.

[0035] Furthermore, the particle size D50 of the tantalum powder is 3-5 um.

[0036] Furthermore, the particle size D90 of the tantalum powder is 6-9 um.

[0037] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a low-oxygen ultrafine tantalum powder, the oxygen content of the tantalum powder is less than 2000ppm, and the difference between the particle size D90 and D50 of the tantalum powder is 2-5um, indicating that the particle size distribution is narrow, the powder is uniform, the particle size of the tantalum powder is fine, and the performance is stable, which can meet the application fields where metallurgical-grade powder has higher requirements on particle size and oxygen content.

[0038] The method for preparing low-oxygen ultrafine tantalum powder as described above, wherein the low-oxygen ultrafine tantalum powder is prepared by the following steps: S1: The high-purity tantalum ingot is subjected to two hydrogenation treatments, and the second hydrogenation temperature is 100°C-400°C lower than the first hydrogenation temperature, so as to increase the contact area between the metal and hydrogen after the high-purity tantalum ingot is defilmed, ensure thorough hydrogenation, and obtain high-brittle high-purity tantalum powder after hydrogenation; S2: Powdering, ball milling, pickling, filtering and drying the hydrogenated high-brittle high-purity tantalum powder to obtain a first crude tantalum powder; S3: adding a reducing agent to the first crude tantalum powder, and then dehydrogenating and deoxygenating the first crude tantalum powder at 700° C.-900° C. to obtain a second crude tantalum powder; S4: acid-washing, filtering and drying the second tantalum powder crude product to obtain low-oxygen ultrafine tantalum powder.

[0039] Specifically, a high-purity tantalum ingot refers to a tantalum ingot with a tantalum content of 99.995% or more.

[0040] Specifically, for ball milling in S2: a ball mill can be used for grinding, the ball milling time is 2h-8h, the stirrer speed is 100r / min-150r / min, and the ball-to-material ratio is 1:3-5; pickling: a mixed acid of nitric acid and hydrofluoric acid is used for washing to remove metal impurities such as Fe, Ni, Cr, C, and Si. The mixed acid is prepared by adding water to nitric acid with a mass concentration of 65% and hydrofluoric acid with a mass concentration of 40%, wherein the ratio of nitric acid solution, hydrofluoric acid solution, and water is 6:2:15-5:1:25; filtering and washing: placing the material after pickling in a filtering and washing tank for filtering and washing, first filtering and washing with cold water until the conductivity is less than 30μs / cm, then changing to hot water, and then filtering and washing with hot water until the conductivity is less than 30μs / cm, and discharging; drying: drying the filtered and washed material, the drying temperature is 100℃-150℃, the drying time is 10-15h, and the material is sieved with 100-200 mesh after drying.

[0041] Specifically, in S4, the pickling is specifically as follows: the second tantalum powder crude product is washed with a mixed acid of nitric acid and hydrofluoric acid to remove metal impurities such as iron, Ni, Cr, C, and Si, wherein the mixed acid is prepared by adding water to nitric acid with a concentration of 65% and hydrofluoric acid with a concentration of 40%, wherein the ratio of nitric acid solution, hydrofluoric acid solution, and water is 6:2:15 to 5:1:25; the filtering is as follows: the material obtained after the pickling is placed in a filtering tank for filtering, first filtering with cold water until the conductivity is less than 20μs / cm, then changing to hot water, and then filtering with hot water until the conductivity is less than 20μs / cm, and discharging the material; drying: drying the filtered material, the drying temperature is 100℃-150℃, the drying time is 10-15h, and the material is sieved with 100-200 mesh after drying to obtain low-oxygen ultrafine tantalum powder.

[0042] Furthermore, in the step S1, the first hydrogenation treatment is carried out at a holding temperature of 1000°C-1100°C for 4h-6h, and the second hydrogenation treatment is carried out at a holding temperature of 700°C-900°C for 8-12h.

[0043] Furthermore, sealing and vacuum replacement are required before hydrogenation. Furthermore, in the step S1, the high-purity tantalum ingot is only in contact with hydrogen and not with other gases during the two hydrogenation processes.

[0044] Furthermore, in the step S1, the heating rate of the first hydrogenation treatment is 20°C / min-30°C / min to provide sufficient energy for hydrogen atoms to destroy the oxide layer on the surface of the tantalum powder, and the heating rate of the second hydrogenation treatment is 5°C / min-10°C / min.

[0045] Furthermore, in the step S3, the reducing agent is magnesium powder, and the amount of the magnesium powder added is 0.5-2.0% of the weight of the first crude tantalum powder.

[0046] Furthermore, in the S3 step, the heating rate of the dehydrogenation and deoxygenation is 10°C / min-20°C / min, and argon gas is introduced for protection during the heating process. Since the first tantalum powder crude product prepared in the present application has fine particle size, large specific surface area and low temperature during the dehydrogenation and deoxygenation process, it will not cause material sintering and will not cause the magnesium oxide particles to be wrapped. The dehydrogenation and deoxygenation are carried out together without affecting the product quality, which can reduce the production cost and increase the production cycle.

[0047] Furthermore, in the step S2, the powder making is specifically as follows: the hydrogenated high-brittle high-purity tantalum powder is crushed, and the hydrogenated high-brittle high-purity tantalum powder is screened to obtain 100-400 meshes of the hydrogenated high-brittle high-purity tantalum powder.

[0048] The use of the present invention is described by the following examples. Embodiment 1:

[0049] S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, and then perform the first hydrogenation: put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 15℃ / min, the maximum insulation temperature is 1100℃, and the insulation is 4-6h. After the heating and insulation is completed, the power is turned off and the temperature is cooled down; the second hydrogenation: after the furnace body is powered off for 12 hours, hydrogenate again, the second heating rate is 10℃ / min, the maximum temperature is 800℃, and the insulation is 10h. Hydrogen is continuously passed throughout the whole process. After the heating and insulation is completed, the power is turned off and the temperature is cooled down, and the furnace is taken out to obtain high-brittleness high-purity tantalum powder after hydrogenation; S2: crush the hydrogenated high-brittle high-purity tantalum powder with a jaw crusher, select 100 mesh sieve, and grind the sieved hydrogenated high-brittle high-purity tantalum powder with a ball mill. The ball milling time is 2h-8h, the mixer speed is 100r / min-150r / min, and the ball-to-material ratio is 1:3-5 to obtain the ball-milled material; then use a mixed acid of nitric acid and hydrofluoric acid to wash the ball-milled material to remove metal impurities such as Fe, Ni, Cr, C, and Si. The mixed acid is composed of nitric acid with a mass concentration of 65% and hydrofluoric acid with a mass concentration of 40%. The method comprises adding water, wherein the ratio of nitric acid solution, hydrofluoric acid solution and water is 6:2:15-5:1:25; placing the pickled material in a filter tank for filtering, first filtering with cold water until the conductivity is less than 30μs / cm, then changing to hot water, and then filtering with hot water until the conductivity is less than 30μs / cm, and discharging the material; drying the filtered material, the drying temperature is 100℃-150℃, the drying time is 10-15h, and after the material is dried, sieving 100-200 mesh, ball milling, pickling, filtering, and drying to obtain a first tantalum powder crude product; S3: Add 0.5% by weight of magnesium powder to the first crude tantalum powder and mix them evenly, then put them into a special reaction bomb, seal them, evacuate them, and put them into a high-temperature furnace for heating at a rate of 20°C / min. During the heating process, argon gas is introduced for protection. The temperature during the heating process is 800°C. After the heating is completed, the power is turned off to cool down, and the powder is taken out of the furnace to obtain the second crude tantalum powder; S4: The second tantalum powder crude product is washed with a mixed acid of nitric acid and hydrofluoric acid to remove metal impurities such as iron, Ni, Cr, C, and Si. The mixed acid is prepared by adding water to nitric acid with a concentration of 65% and hydrofluoric acid with a concentration of 40%, wherein the ratio of nitric acid solution, hydrofluoric acid solution, and water is 6:2:15 to 5:1:25; the material obtained after acid washing is placed in a filter washing tank for filtering, firstly filtered with cold water until the conductivity is less than 20μs / cm, then replaced with hot water, and then filtered with hot water until the conductivity is less than 20μs / cm, and discharged; drying: drying the filtered material at a drying temperature of 100℃-150℃ for 10-15h. After drying, the material is sieved with 100 mesh to obtain a low-oxygen ultrafine tantalum powder sample D. Embodiment 2:

[0050] S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, and then perform the first hydrogenation: put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 15℃ / min, the maximum insulation temperature is 1100℃, and the insulation is 4-6h. After the heating and insulation is completed, the power is turned off and the temperature is cooled to obtain high-brittleness high-purity tantalum powder after hydrogenation; S2: The hydrogenated high-brittle high-purity tantalum powder is crushed by a jaw crusher and sieved with a 100-mesh sieve to obtain a low-oxygen ultrafine tantalum powder sample d.

[0051] Comparative Example 1: S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, then put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 20℃ / min, the maximum insulation temperature is 1100℃, the insulation time is 5h, and hydrogen is continuously passed throughout the whole process. After the heating and insulation is completed, the power is turned off and the temperature is lowered, and the furnace is taken out to obtain high-brittleness high-purity tantalum powder after hydrogenation; The other steps are the same as those in Example 1 to obtain a comparative tantalum powder sample A.

[0052] Comparative Example 2: S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, then put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 15℃ / min, the maximum insulation temperature is 1000℃, the insulation time is 5h, and hydrogen is continuously passed throughout the whole process. After the heating and insulation is completed, the power is turned off and the temperature is lowered, and the furnace is taken out to obtain high-brittleness high-purity tantalum powder after hydrogenation; The other steps are the same as those in Example 1 to obtain a comparative tantalum powder sample B.

[0053] Comparative Example 3: S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, then put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 10℃ / min, the maximum insulation temperature is 1000℃, the insulation time is 5h, and hydrogen is continuously passed throughout the whole process. After the heating and insulation is completed, the power is turned off and the temperature is lowered, and the furnace is taken out to obtain high-brittleness high-purity tantalum powder after hydrogenation; The other steps are the same as those in Example 1 to obtain a comparative tantalum powder sample C.

[0054] Comparative Example 4: S1: Put the high-purity tantalum ingot into a special reaction bomb, seal it, evacuate it and replace it, then put the reaction bomb into a high-temperature furnace to heat it up, pass hydrogen during the heating process, the heating rate is 15℃ / min, the maximum insulation temperature is 700℃, the insulation time is 5h, and hydrogen is continuously passed throughout the whole process. After the heating and insulation is completed, the power is turned off and the temperature is lowered, and the furnace is taken out to obtain high-brittleness high-purity tantalum powder after hydrogenation; The other steps are the same as those in Example 1 to obtain a comparative tantalum powder sample E.

[0055] Low oxygen ultrafine tantalum powder sample D, low oxygen ultrafine tantalum powder sample d, comparative tantalum powder sample A, comparative tantalum powder sample B, comparative tantalum powder sample C, and comparative tantalum powder sample E were respectively subjected to impurity content detection, particle size distribution detection, and scanning electron microscope detection. The detection instruments are shown in Table 1, the sample chemical impurity content detection results are shown in Table 2, and the particle size distribution diagram is shown in Table 3. Figure 1-6 As shown in the scanning electron microscope image Figure 7-12 shown.

[0056] Table 1

[0057] Table 2

[0058] From Table 2, Figures 1 to 12 It can be seen that the low-oxygen ultrafine tantalum powder sample D prepared in Example 1 has a low oxygen content and low impurity contents of Fe, Ni, Cr, and C. The smaller the difference between D90 and D50, the narrower the particle size distribution of the tantalum powder and the better the uniformity. By comparing the low-oxygen ultrafine tantalum powder sample D, the low-oxygen ultrafine tantalum powder sample d, and the comparative tantalum powder sample A, it can be seen that although D50 is small in the first hydrogenation, the larger D90 is, the larger the difference between D90 and D50 is, the larger the tantalum powder particle size is, and the worse the uniformity is. By comparing the low-oxygen ultrafine tantalum powder sample d, the comparative tantalum powder sample A, the comparative tantalum powder sample B, the comparative tantalum powder sample C, and the comparative tantalum powder sample E, it can be seen that in the first hydrogenation process, the particle size of the tantalum powder is reduced by adjusting the heating rate and the hydrogenation temperature, but the reduction is limited.

[0059] What is disclosed above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A low-oxygen ultrafine tantalum powder, characterized in that: The oxygen content of the tantalum powder is less than 2000 ppm, and the difference between the particle size D90 and D50 of the tantalum powder is 2-5 um.

2. The low-oxygen ultrafine tantalum powder according to claim 1, characterized in that: The particle size D50 of the tantalum powder is 3-5 um.

3. The low-oxygen ultrafine tantalum powder according to claim 1 or 2, characterized in that: The particle size D90 of the tantalum powder is 6-9 um.

4. The method for preparing low-oxygen ultrafine tantalum powder according to claim 1, characterized in that: The low-oxygen ultrafine tantalum powder is prepared by the following steps: S1: The high-purity tantalum ingot is subjected to two hydrogenation treatments, and the second hydrogenation temperature is 100°C-400°C lower than the first hydrogenation temperature, so as to increase the contact area between the metal and hydrogen after the high-purity tantalum ingot is defilmed, ensure thorough hydrogenation, and obtain high-brittle high-purity tantalum powder after hydrogenation; S2: Powdering, ball milling, pickling, filtering and drying the hydrogenated high-brittle high-purity tantalum powder to obtain a first crude tantalum powder; S3: adding a reducing agent to the first crude tantalum powder, and then dehydrogenating and deoxygenating the first crude tantalum powder at 700° C.-900° C. to obtain a second crude tantalum powder; S4: acid-washing, filtering and drying the second tantalum powder crude product to obtain low-oxygen ultrafine tantalum powder.

5. The method for preparing low-oxygen ultrafine tantalum powder according to claim 4, characterized in that: In the step S1, the first hydrogenation treatment is carried out at a holding temperature of 1000° C.-1100° C. for 4 h-6 h, and the second hydrogenation treatment is carried out at a holding temperature of 700° C.-900° C. for 8 h-12 h.

6. The method for preparing low-oxygen ultrafine tantalum powder according to claim 4, characterized in that: In the step S1, the high-purity tantalum ingot is only in contact with hydrogen and not with other gases during the two hydrogenation processes.

7. The method for preparing low-oxygen ultrafine tantalum powder according to claim 5, characterized in that: In the step S1, the heating rate of the first hydrogenation treatment is 20°C / min-30°C / min, and the heating rate of the second hydrogenation treatment is 5°C / min-10°C / min.

8. The method for preparing low-oxygen ultrafine tantalum powder according to claim 4, characterized in that: In the step S3, the reducing agent is magnesium powder, and the amount of the magnesium powder added is 0.5-2.0% of the weight of the first crude tantalum powder.

9. The method for preparing low-oxygen ultrafine tantalum powder according to claim 4, characterized in that: In the step S3, the heating rate of the dehydrogenation and oxygen reduction is 10°C / min-20°C / min, and argon gas is introduced for protection during the heating process.

10. The method for preparing low-oxygen ultrafine tantalum powder according to claim 4, characterized in that: In the step S2, the powder making is specifically as follows: the hydrogenated high-brittle high-purity tantalum powder is crushed and screened to obtain the hydrogenated high-brittle high-purity tantalum powder of 100-400 meshes.

Citation Information

Patent Citations

  • High-purity tantalum powder and preparation method therefor

    CN105377481A

  • Method for the production of niobium and tantalum powder

    CN101774018A

  • Fine Tantalum Powder And Manufacturing Method Thereof

    CN107427925A

  • Refractory metal powder, preparing method thereof and metal product

    CN108788129A

  • High-purity tantalum powder and preparation method thereof

    JP2018123432A